PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING, MEDIA PEMBELAJARAN POWER POINT DAN PRESTASI BELAJAR - Ria Yusfita Ernawati (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2017)
The study aimed to observe the Influence of Learning Model Discovery Learning and Learning Media Power Point to the Student Achievement of Social Science 5th Grade Student at SDN 1 Banjarjo, Pudak, Ponorogo. The study used population all students of class V SDN 1 Banjarjo, Pudak, Ponorogo totaling 30 students. But only 30 students was taken as sample, using total sampling technique. The instrument used was questionnaires. The Results of evaluator analysis and assay statistic proves that the naught hypothesis (Ho) refused and the alternative hypothesis (Ha) is accepted. This study means that the partial application of learning models Discovery learning and Learning Media Power Point have a significant effect on Student Achievement of Social Sciences, with tcount respectively 3.782 and 0.888 is greater than ttable which is 2.042 and 0.662. The statistical analysis also result that simultaneous application of learning models Discovery learning and Learning Media Power Point have a significant effect on Student Achievement of Social Sciences, with Fcount 7.621 greater than Ftable which is 3.34. beside of that from bifiliar linear regression evaluator is known that the application of Discovery learning as learning model and Power Point as Learning Media have a significant influence on student learning achievement in social studies, with the Rvalue of 0.601 with constant coefficient of 63.115. It is concluded that there is significant influence between the application of Discovery learning as learning model and Power point as Learning Media on the Student Achievement of Social Sciences 5th grade students at SDN 1 Banjarjo, Pudak, Ponorogo.